PENETAPAN KADAR FLAVONOID FRAKSI ETIL ASETAT DAUN KARET KEBO (Ficus elastica) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Asriani Suhaenah; Mamat Pratama; A.Hesti Wulandasari Amir (As-Syifaa Jurnal Farmasi, 2021)
Rubber plant (Ficus elastica) is a plant that has been widely used as traditional medicine. The leaves of this plant are used as medicine for coughing up blood, laxative urine, relieving pain and improving blood circulation. Various kinds of properties and benefits of the rubber plant (Ficus elastica) cannot be separated from  the compounds contained in it such as saponins, polyphenols, and flavonoids.  The purposes of this research is to determine the flavonoid total content in the ethyl acetate fraction of the rubber leaves (Ficus elastica). Simplicia was extracted by maceration method, using 96% ethanol solvent for 3x24 hours and partitioned with a mixture of 96% ethanol - aquadest (2:3) and ethyl acetate as a solvent. Determination of flavonoid content using UV-Vis spectrophotometry method , with a maximum wavelength of 438 nm, using quercetin as a comparison. The results of this research obtained that the total flavonoid content in the ethyl acetate fraction of  rubber leaves (Ficus elastica) was an average of 74,345 mgQE/g fraction.